The Meaning of Verba Omou (思う) As Polysemia In Japanese Sentences - Nunik Nur Rahmi Fauzah; Citra Dewi; Megita Rubiana Sabella (Ilmu Inovasi Nusantara, 2026)
This study investigates the polysemy of the Japanese verb omou (思う) by addressing the following research questions: (1) What are the basic and extended meaning pof the verb omou (思う) and (2) How do language styles influence the expansion of its meanings? The data was collected by collecting sentences containing omou (思う) verbs from NHK Easy News Web news articles. The data was analyzed by determining the classification of the meaning of omou (思う) verbs. Examples of data to be analyzed based on the purpose are classified based on the type of meaning. Then, the relationship between the meanings possessed by omou (思う) verbs is described by analyzing the language styles that affect the expansion of their meanings. From the data sources obtained, it is concluded that there are 5 meanings of omou (思う) verbs, namely 1) thinking; 2) assuming; guessing; imagining; 3) feeling; 4) expecting; wanting; and 5) determining; deciding. The expansion of meaning that occurs is influenced by 2 language styles, namely metaphor and metonymy.